Mecanismos de seleção de Gale-Shapley dinâmicos em Universidades Brasilieiras; SISU, SISU (Alpha) e SISU (beta) - Abreu, Luís Carlos Martins (2013)
In Brazil, the quest for reducing observed inefficiencies in the allocation of seats in higher education institutions through traditional examination (Vestibular) led to the formulation and alternative mechanism of selection: the Unified Selection System (SISU), created in 2010. Technically speaking, the mechanism is a matching algorithm with the following characteristics: i) each student who receives an offer decides to accept or reject the received offer; ii) rejections of offers prompt new proposals; iii) proposals are accepted temporarily, and each offer can be “replaced” by an offer considered “better”. That is, the SISU is a mechanism similar to the Deferred Acceptance Algorithm (Gale-Shapley Algorithm). Despite the importance of SISU, the economic literature on the subject is basically nonexistent. In this sense, this dissertation sought, in light of game theory, to understand and characterize the incentives provided by SISU through two developed theoretical mechanisms, the SISU and SISU . Both are modeled as dynamic matching mechanisms. We characterize undominated strategies for SISU and SISU . Using SISU as the best approximation available to SISU, we conclude that the introduction of SISU showed a significant improvement on Vestibular in terms of gains of efficiency from matching between students and courses.